Secure Communications Based on Dual Synchronization of Cross - Coupled Different Chaotic Oscillators - Tahir, Fadhil Rahma (Basrah Journal for Engineering Sciences, 2010)
The dual synchronization of two different pairs of chaotic oscillators: one pair of Duffing oscillators and one pair of Murali-Lakshmanan-Chua (ML-Chua) circuits has been achieved by numerical simulations. The cross-coupling method, where the difference in the voltage between the sum of the two master oscillators' voltages and one of the slave oscillator voltages is injected 10 the other slave oscillator as an electrical current, for the dual synchronization has been used. The accuracy of synchronization of chaos is numerically obtained by calculating the root mean square error (RMSE). A communication scheme is presented, utilizing the chaotic masking (CMS) technique. Encoding and decoding of a message based on dual synchronization of chaos has been demonstrated.